P811 Combination biological or small molecule therapy in patients with refractory inflammatory bowel disease: a multicenter Brazilian experience. (30th January 2023) - Feitosa, F; Parra, R; Queiroz, N; Flores, C; Schiavetti, B; Azevedo, M; Porto Alegre Rosa, C; Chebli, L; Chebli, J
Abstract: Background: This preliminary study describes the Brazilian experience on dual biologic therapy or small molecule combined with a biologic therapy in patients with inflammatory bowel disease (IBD) refractory to multiple biologics. Methods: We identified patients from 6 IBD centers in Brazil between April 2020 and November 2022 who received treatment with a combination of two biologics or a biologic and a small molecule drug due to refractory disease or concomitant immunomediated condition. The primary endpoint was clinical remission at week 16, defined as a total Mayo score of ≤2 for UC and Harvey-Bradshaw Index (HBI) <4 for CD. Secondary endpoints were improvement in disease activity scores and biomarkers. Adverse events were monitored and summarized descriptively. Results: Twenty-nine patients were identified (69% CD, n=20), 51.8% female, mean age 38.8 years old [SD= ± 14.8 years]). Seventy per cent (n=14) had penetrating behavior among CD patients. Twenty-seven had failed to, at least, one anti-TNF; 79.9% had failed to ustekinumab (UST), and 34.5% to vedolizumab (VEDO). Twenty-six patients were treated with combination advanced therapy due to loss of response to biologics and three patients had concomitant ankylosing spondylitis. The most common combination used was UST+ADA (n=12, 41.4%), followed by UST+VEDO (n=6, 21.7%). Mean treatment time was 53.8 weeks (SD= 40.4 weeks, CI 95% [37.5 – 70]). At week 16, clinical remission rates were 80% and 66% for CD and UC, respectively. All patients under VEDO + UST combination achieved clinical remission at 16w, in both diseases. Baseline HBI mean was 10.8 (SD= ± 3.6 points; CI 95% [9.1- 12.5]), decreasing to a mean of 5.5 at week 16 (SD= ± 3.5 points; CI 95% [3.8 - 7.2]) and plateauing at 7 by week 24 (SD= ±5.4 CI 95% [3.4- 10.6]). There was a notable decrease in HBI at week 16 (p< 0.001) and a significant decrease at week 24 (p= 0.02) compared to baseline. Mean CRP at week 16 was significantly lower than baseline in CD (17.4mg/dL vs 5.5 mg/dL, p=0.001) and numerically lower in UC (from 14.3mg/dL to 9.9mg/dL, p= 0.5). Fecal calprotectin decreased from 2509mcg/g to 1472mcg/g in both groups (p=0, 2). In addition, all patients with ankylosing spondylitis showed symptomatic remission. No new safety signals were identified during follow-up Conclusion: Despite combination of advanced therapies in IBD is not yet recommended by treatment guidelines, this strategy seems to be a promising option for patients with refractory IBD or concomitant autoimmune disease. Our data indicate that further investigation in this direction is worthwhile.